1998
DOI: 10.3171/jns.1998.89.4.0585
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke pain control by chronic motor cortex stimulation: neurological characteristics predicting a favorable response

Abstract: These findings suggest that the pain control afforded by MC stimulation requires neuronal circuits that are maintained by the presence of intact corticospinal tract neurons originating from the MC. Preoperative evaluation of motor weakness of the painful area appears to be useful for predicting a favorable response to MC stimulation in the control of poststroke pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
126
0
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(135 citation statements)
references
References 61 publications
4
126
0
5
Order By: Relevance
“…with all contacts on the M1 or S1 Rasche et al, 2006). Moreover, no polarity-related difference in pain relief is seen for most patients with epidural electrodes (Katayama et al, 1998).…”
Section: Electrode Implantationmentioning
confidence: 93%
“…with all contacts on the M1 or S1 Rasche et al, 2006). Moreover, no polarity-related difference in pain relief is seen for most patients with epidural electrodes (Katayama et al, 1998).…”
Section: Electrode Implantationmentioning
confidence: 93%
“…[23][24][25][26][27]59 A review of their publications indicates a total of 88 patients (some patients apparently are included in multiple reports). They not only explored MCS alone but also compared it to DBS and SCS as separate therapies and in combination.…”
Section: Introductionmentioning
confidence: 99%
“…These initial results nonetheless helped spur further investigation into MCS for pain. In 1998, Katayama et al 25 reported 23 of 31 poststroke patients having satisfactory pain control in initial results; at 2 years, however, pain control was satisfactory in only 8 of the 23.…”
Section: Introductionmentioning
confidence: 99%
“…Poststroke pain responds to MCS, with 50-70% of patients achieving relief. 8,15,20) Excellent results have also been reported in the treatment of trigeminal neuropathic pain, with 75-100% of patients achieving pain relief. 6,13,14,18) A prospective study used MCS to treat 10 patients with neuropathic facial pain attributed to surgical trigeminal root injury, poststroke, postherpetic, or no cause.…”
Section: Tnmentioning
confidence: 91%